Introduction to sensors for ranging and imaging - Brooker, Graham (SciTech Publishing, 2009)
This book has sixteen chapters. The first chapter deals with introduction to sensing. The second chapter covers signal processing and modulation. The third chapter is for IR radiometer and image intensifiers. The fourth chapter discussed millimetre wave radiometer. The fifth chapter deals with active ranging sensors. The sixth chapter is for active imaging sensors. The seventh chapter covers signal propagation. The eighth chapter discusses target and clutter characteristics. The ninth chapter covers detection of signals in noise. The tenth chapter deals with Doppler measurement. The eleventh chapter is for high range-resolution techniques. The twelfth chapter discusses high angular-resolution techniques. The thirteenth chapter covers range and angle estimation and tracking. The fourteenth chapter deals with tracking moving targets. The fifteenth chapter is for radio frequency identification and transponders. The last chapter is dedicated to tomography and 3D imaging.